In vitro anticancer activity and oxidative molecular damage by cannabidiol administered alone and in combination with epirubicin. Issue 1 (1st January 2021) - Zhelyazkova, Margarita; Hristova-Avakumova, Nadya; Todorov, Lozan; Momekov, Georgi
Abstract: Evidence suggests that the non-psychotropic phytocannabinoid cannabidiol (CBD) has anticancer activity on different cell lines and in animal models. The DNA-damaging drug epirubicin (EPI) is widely used for the treatment of malignant tumours. In this study we examined the effectiveness of CBD administered alone and in combination with EPI on HL-60, HL-60/Dox and MCF-7 cell-lines. We applied MTT reduction assay and the bioinformatics model of Chou-Talalay for experimental design of combination chemotherapy to evaluate the anticancer activity of several epirubicin-based combinations with CBD in various treatment regimens. In addition, we studied the efficacy of the co-treatment regimens to induce changes in two in-vitro model systems containing superoxide radical and 2-deoxyribose. We then evaluated the effectiveness of EPI plus CBD. The maximal growth cell inhibition ∼90% in leukemic and breast cancer cells was measured at the peak tested concentrations 2.5 EPI plus 25 CBD, µmol/L. The combination index (CI) value showed the presence of slightly expressed antagonism between EPI and CBD in most cases. The antiproliferative effect of the combination was reduced by only 8–10% vs. the inhibition induced by either EPI or CBD alone. We determined that the slight antagonism correlated positively to the registered dosage and decreased the extent of deoxyribose oxidative damage by using the enhanced chemiluminescent method with superoxide radicals. The therapeutic value of the combination of EPI plus CBD mainly consists of its high antiproliferative effect and the possibility to reduce the total dose on leukaemia-transformed cells by a factor of two. Supplemental data for this article is available online at https://doi.org/10.1080/13102818.2021.1996270 .